2019
DOI: 10.2166/wst.2019.384
|View full text |Cite
|
Sign up to set email alerts
|

Dominant decomposition pathways in pit latrines: a commentary

Abstract: In a recent article an assessment of decomposition within pit latrines measured with regard to chemical oxygen demand (COD) reductions was reported on. Some fundamental concerns were raised with regard to a key assumption of the study. The alternative perspective that is presented here does not support the study's conclusion that anaerobic processes are the dominant decomposition pathway in pit latrines. Furthermore, it is argued that their analysis and some implications of their data interpretation can be vie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The current IPCC GHG estimation methodology has been used as the basis for calculations in this analysis [26]. However, this methodology has significant limitations as GHG emissions vary widely among waste treatment technologies, especially among decentralized sanitation, depending on the biogeochemical conditions, operating conditions and associated collection and discharge systems [2,13,19,27]. As such, this analysis made provisions for refinement and comparison of the current IPCC model with improved and experimentally verified emission factors (EFs).…”
Section: Model Descriptionmentioning
confidence: 99%
“…The current IPCC GHG estimation methodology has been used as the basis for calculations in this analysis [26]. However, this methodology has significant limitations as GHG emissions vary widely among waste treatment technologies, especially among decentralized sanitation, depending on the biogeochemical conditions, operating conditions and associated collection and discharge systems [2,13,19,27]. As such, this analysis made provisions for refinement and comparison of the current IPCC model with improved and experimentally verified emission factors (EFs).…”
Section: Model Descriptionmentioning
confidence: 99%
“…Because onsite sanitation facilities may be highly diverse within and across settings of interest, extending the principles of WBE to fecal sludges requires standardized methods for sampling. The physical [31,32] and microbial [32][33][34] dynamics of fecal sludges have increasingly been studied, but attempts to characterize the spatial distribution of enteric pathogens in onsite technologies have been primarily limited to fecal indicator bacteria [35]. It is unclear how the intra-pit depth (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Eekert et al [39] suggested that the anaerobic biodegradation of solids in pit latrines could be improved with the addition of freshwater. However, it has also contended that this practice could hinder aerobic biodegradation mechanisms in pit latrines [40]. Furthermore, in general, there is a growing recognition of declining freshwater availability at the global and local scales and, as such, waterborne sanitation systems are potentially advantageous in all contexts: low-, middle-, and high-income countries [41,42].…”
Section: Discussionmentioning
confidence: 99%